PERSPECTIVES OF BELTEI INTERNATIONAL SCHOOL STUDENTS TOWARD PURSUING HIGHER EDUCATION AT BELTEI INTERNATIONAL UNIVERSITY - Hour, Vannak (Srawung: Journal of Social Sciences and Humanities, 2025)
All K12 graduates in Cambodia must choose the suitable university for furthering their study. Therefore, this study analyzes why the majority of BELTEI International School (BELTEI IS) alumni chose other universities over BELTEI International University (BELTEI IU), despite the institutional relationship. BELTEI IS is one of Cambodia's largest private school networks, while BELTEI IU, its higher education equivalent, provides degrees in 13 faculties and 45 specialties. However, only a tiny fraction of BELTEI IS graduates (11% at Campus 1 and 5% at Campus 2) enrolled at BELTEI IU for the 2024-2025 academic year. This phenomenological research, which used purposive sampling and in-depth semi-structured interviews with 80 BELTEI IS graduates, investigates the factors that influence their university decisions. According to the findings, students chose other schools mostly because of perceived better employment prospects (14.8%), family/friend recommendations (12.7%), and a higher reputation/ranking (11.3%). BELTEI IS staff had little impact over these decisions (82.5% indicated no influence). Participants stressed the importance of BELTEI IU offering a distinctive campus atmosphere, advanced academic programs, greater research and innovation possibilities, and improved teaching quality. They also stressed the need for a student-centered approach, greater career assistance, and budgetary transparency. These elements, together with university culture and value offer, are critical in decision-making for future professional success.